Experiences from the Russian-Ukrainian War in Respect of Civil Defense - Łydka, Andrzej (Roczniki Nauk Społecznych, 2025)
The aim of the article is to familiarize the reader with the organization and implementation of civil defence in the conditions of regular conventional war in Ukraine. The main research question is: What is the Ukrainian experience regarding the consequences of Russian aggression for society and the ability of civil defence to respond to attacks that can be used in the construction of Polish civil defence? This data may be useful in building a civil defence system in Poland. In order to answer the research question, reports on civil defence issues in Ukraine were analysed. The research indicates that in the pre-war period, the possible effects of the Russian aggressor’s actions on the civilian population were not correctly estimated, which resulted in problems with the preparation and evacuation of the population and the organization of the shelter system. When the war was on, the problematic provision of psychological support for civil defense personnel and the preparation of a system of “points of invincibility” for the civilian population considered. The article also contains recommendations for the Polish civil defense system.